2021
DOI: 10.21037/jgo-20-424
|View full text |Cite
|
Sign up to set email alerts
|

Proton stereotactic body radiation therapy for liver metastases—results of 5-year experience for 81 hepatic lesions

Abstract: Background: To report on our institutional experience using Proton stereotactic body radiation therapy (SBRT) for patients with liver metastases.Methods: All patients with liver metastases treated with Proton SBRT between September 2012 and December 2017 were retrospectively analyzed. Local control (LC) and overall survival (OS) were estimated using the Kaplan-Meier method calculated from the time of completion of Proton SBRT. LC was defined according to Response Evaluation Criteria in Solid Tumors (RECIST) gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…PBT can add to the safety of liver irradiation, particularly in the setting of multiple LM, and Coffman et al. demonstrated no cases of RILD in 46 patients treated to 81 LM while achieving an LC of 92% 69 …”
Section: Discussionmentioning
confidence: 99%
“…PBT can add to the safety of liver irradiation, particularly in the setting of multiple LM, and Coffman et al. demonstrated no cases of RILD in 46 patients treated to 81 LM while achieving an LC of 92% 69 …”
Section: Discussionmentioning
confidence: 99%
“…Protons can be used to reduce the integral liver dose associated with photon SBRT, potentially minimizing the risk of hepatic toxicity associated with radiotherapy [41] . A retrospective single-institutional review of stereotactic body proton therapy (SBPT) for 81 liver metastases in 46 patients, 56.5 % of whom had two or more treated tumors, reported no grade 3 + toxicities [42] . Conformality and toxicity of SBPT with passive-scatter technology may be further improved by utilizing modern radiotherapy techniques for planning (e.g.…”
Section: Seventh-inning Stretchmentioning
confidence: 99%
“…It is important to note that there are limited randomized data comparing SBRT to other local modalities for the treatment of liver metastases. Several retrospective and prospective studies reported favorable LC rates following SBRT for limited liver metastases [2,15,[20][21][22][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Table 1 summarizes key retrospective and prospective studies published in the last two decades.…”
Section: Comparison Of Lc Of Liver Metastases Following Sbrt and Othe...mentioning
confidence: 99%